Numerical Study of an Array of Evaporating Droplets Through a Crossflow - Barata, Jorge M M (2012)
The present paper presents a numerical study on evaporating droplets through a turbulent crossflow. The aim of this study is to evaluate and improve an Eulerian/Lagragian approach to account for turbulent dispersion, evaporation and coupling between both processes in spray systems. A method developed to study isothermal turbulent dispersion is extended to the case of an array of evaporating droplets, using two different evaporation models. Droplet diameter, temperature and mass fraction distributions were found to be strongly dependent on the evaporation models used.